Hospital Dissemination of tst-1-Positive Clonal Complex 5 (CC5) Methicillin-Resistant Staphylococcus aureus - Wang, Min; Zheng, Yi; Mediavilla, Jose. R.; Chen, Liang; Kreiswirth, Barry. N.; Song, Yajun; Yang, Ruifu; Du, Hong (Frontiers in Cellular and Infection Microbiology, 2017)
Methicillin-resistant Staphylococcus aureus (MRSA), is one of the most prevalent clinical pathogens isolated from hospital settings, and has increasingly identified in community settings. In China, the SCCmecIII-ST239 strains are disseminated in different geographic regions, accounting for > 75% of all MRSA isolates in some national studies. Here we characterized 150 non-duplicate MRSA isolates collected from February 2012 to May 2013 in a tertiary hospital in Suzhou, Eastern China, to explore the molecular epidemiology. All isolates were characterized by spa typing, SCCmec typing, and detection of genes encoding Panton-Valentine leukocidin (PVL) and toxic shock syndrome toxin (TSST-1). Representative genotypes were also subjected to multilocus sequence typing (MLST). Antibiotic susceptibility testing was performed using BD Phoenix™ Automated Microbiology System. Molecular typing identified 11 clonal complex (CC) and 28 spa types, with the CC5-spa t002 (29.3%) and CC239-spa t037 (14.7%) being the most prevalent. SCCmec types II, III, IV and V were identified in 33.3%, 21.3%, 23.3% and 21.3% of all isolates, respectively. PVL genes (lukF/S-PV) were detected in 11.3% of all isolates and from 6 CCs (5, 8, 59, 88, 239, and 398). The TSST-1 gene (tst) was detected in 18.0% of the all isolates, predominantly in CC5 (96.3%). All the tst-1-positve CC5 isolates were spa t002. 18 patients died within 30 days of hospitalization, and the in-hospital 30-day mortality was 12.0%. Multivariable analysis showed that 60 years old (odds ratio [OR]=7.2, P=0.026), cancer diagnosis (OR=9.6, P=0.022), and MRSA isolate carriage of tst-1 (OR=62.5, P<0.001) were independent factors associated with 30-day mortality. Our study revealed unique MRSA dissemination patterns in our hospital in comparison to those of other regions in China. The finding that tst-1-positive CC5 strains were associated with higher mortality highlights the need for strict infection control measures in order to prevent further spread of these strains in our hospital, as well as others.